Sex Bias in the Clinical Diagnosis of ADHD: A Critical Review - Farzad Salehpour; Francisco Gonzalez-Lima (Journal of Clinical Medicine, 2026)
Background: Attention-deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder that manifests differently across sexes, potentially impacting symptomatology, diagnosis, and treatment. Nevertheless, these legitimate sex differences in ADHD are further shaped by multiple sources of bias that distort prevalence estimates and clinical recognition. Methods: This critical review synthesizes evidence on a variety of factors, including sampling bias, referral bias, DSM criteria, and diagnostic overshadowing, that may contribute to the under-recognition and misdiagnosis of ADHD in females. Results: Studies suggest that sampling and referral biases inflate male representation by overemphasizing disruptive behaviors and underrecognizing inattentive presentations in females. Item-level symptom endorsement differences indicate that several DSM-5 criteria map more closely onto male-typical behaviors, reducing sensitivity to female-specific manifestations. Diagnostic thresholds, age-of-onset, and pervasiveness criteria further disadvantage females, whose symptoms are often less overt or more context-dependent. Recognition bias and diagnostic overshadowing by mood and anxiety disorders contribute to missed or delayed diagnoses. Conclusions: Together, these findings highlight that observed sex differences in ADHD reflect not only true psychobiological variation but also systematic biases in assessment and diagnosis, underscoring the need for more sex-sensitive diagnostic frameworks and improved clinical awareness. The extent of these diagnostic disparities may also vary across cultural contexts and healthcare systems, including differences in symptom perception, referral pathways, and access to specialist assessment.